Contrasting State‐Dependent Effects of Natural Forcing on Global and Local Climate Variability - Ellerhoff, Beatrice; Kirschner, Moritz J.; Ziegler, Elisa; Holloway, Max D.; Sime, Louise; Rehfeld, Kira (Geophysical Research Letters, 2022)
Natural forcing from solar and volcanic activity contributes significantly to climate variability. The post-eruption cooling of strong volcanic eruptions was hypothesized to have led to millennial-scale variability during Glacials. Cooling induced by volcanic eruption is potentially weaker in the warmer climate. The underlying question is whether the climatic response to natural forcing is state-dependent. Here, we quantify the response to natural forcing under Last Glacial and Pre-Industrial conditions in an ensemble of climate model simulations. We evaluate internal and forced variability on annual to multicentennial scales. The global temperature response reveals no state dependency. Small local differences result mainly from state-dependent sea ice changes. Variability in forced simulations matches paleoclimate reconstructions significantly better than in unforced scenarios. Considering natural forcing is therefore important for model-data comparison and future projections. Key Points We present Glacial/Interglacial climate simulations and quantify effects of time-varying volcanic and solar forcing on climate variability The mean global and local response to these forcings is similar in Glacial and Interglacial climate, suggesting low state dependency In both climate states, modeled temperature variance agrees better with palaeoclimate data when volcanic and solar forcing is included